Growth, Production and Bioactive Content of Several Black Cumin (Nigella sativa L.) Accessions With Different Harvesting Times in a D3 Type Climate Regime - Cahyo, Septian Dwi; Kurniawati, Ani; Faridah, Didah Nur; Ghulamahdi, Munif (Journal of Tropical Crop Science, 2020)
Black cumin (Nigella sativa L.) is a species Ranunculaceae family which grows in the Middle Eastern and Southern Mediterranean countries. Black cumin is also known as habbatus sauda , or kalonji in South Asia. Black cumin seeds are used as spice traditional medicine; the essential oil compound in the seeds has been identified as thymoquinone. Thymoquinone has a potent antioxidant effect, which could protect organs from oxidative damage by generating free radical agents. Indonesia is one of the most geographically diverse country in the world. Some regions have scattered low and high plains, abundant sunlight, evenly distributed rainfall throughout the year, and highly diverse soil types. The purpose of this study was to study the growth, production, thymoquinone and thymol content of several accessions of black cumin with different harvesting time in D3 type climate regimes. The research was conducted from April to September 2019 in Ngadirejo Village, Sukapura District, Probolinggo Regency, East Java with an altitude of 1.680 m above sea level. The experiment used a randomized complete block design with one factor for the vegetative phase, namely accession (“American”, “Indian”, “Kuwait”, and “Slovenian”) and two factors for the generative phase, namely accession and harvesting time. The harvesting time of black cumin was conducted at 6, 7, and 8 weeks after the anthesis. “Indian” and “Slovenian” accession demonstrated the best vegetative growth, whereas “Indian” had the highest capsules number per plant, seeds weight per plant, and the highest estimated production compared to other accessions (603 kg seeds. ha-1). “American”, “Indian” and “Kuwait” accessions are well adapted in D3 type climate. The harvesting time of 7 to 8 weeks from anthesis was shown to be optimal for all accessions. Thymoquinone and thymol content for the four accessions was circa 349.64– 3,030.45 μg. g-1 of seeds and 385.56 – 2,003.46 μg.g-1 of seeds, with potential production values of 0.18 - 1.83 kg.ha-1 and 0.19 - 0.45 kg.ha-1, respectively. The optimal harvesting time to maximize seed production was unaffected by the black cumin accession.